Efeito da exposição ao cádmio sobre dano oxidativo, morte celular e comportamento de zebrafish - Igansi, Gustavo Nascente (2012)
Cadmium is considered the seventh most dangerous substance in the environment and is classified as carcinogen type I, potentially affecting a wide range of living organisms, including humans. In addition to its wide systemic impact and potential lethality, cadmium has been associated to neurobehavioral defects that may also compromise animals ecological status and survival. Despite its potential impact, the comprehension of cellular and molecular mechanisms underlying cadmium deleterious effects on animals behavior is still scarce. This study aimed to evaluate the behavioral effects of cadmium for 1 or 7 days at environmentally relevant concentrations (10 μg/L, 100 μg/L and 1000 μg/L) on zebrafish and to analyze brain oxidative stress and apoptotic markers. Cadmium-exposed zebrafish exhibited a generalized increase in locomotor activity after 1 and 7 days of treatment at all doses in all parameters evaluated, including distance travelled in a 5-min. evaluation period, mean speed and mobile periods. This hyperlocomotory effect significantly compromised animals general performance in exploring a new environment, which was evident in all cadmium exposed animals decreased path efficiency and altered distribution on the water column. Additionally, our results confirmed previous reports of increased oxidative damage in fishes exposed to cadmium and specifically demonstrated higher levels of damaged proteins in brain samples of animals exposed to cadmium at 100 μg/L for 1 day and at 10 μg/L for 7 days when compared to their respective control groups. Lipid peroxidation was also significantly increased in animals brain after 1 day cadmium exposure at 100 μg/L. Real-Time PCR analysis of transcripts for p53 and bax were not altered after 1 day cadmium exposure, but significantly increased after 7 days. Our results present evidence of cadmium deleterious effects on zebrafish cognitive functions and raise attention to the fact that its manifestation appears already after a one day exposure to 10 μg/L, a concentration accepted by most international regulating agencies